On Eulerian orientations of even-degree hypercubes - Levit, Maxwell; Chandran, L. Sunil; Cheriyan, Joseph (Elsevier, 2018)
It is well known that every Eulerian orientation of an Eulerian 2k-edge connected (undirected) graph is strongly k-edge connected. A long-standing goal in the area is to obtain analogous results for other types of connectivity, such as node connectivity. We show that every Eulerian orientation of the hypercube of degree 2k is strongly k-node connected.
The final publication is available at Elsevier via https://dx.doi.org/10.1016/j.orl.2018.09.002 © 2018. This manuscript version is made available under the CC-BY-NC-ND 4.0 license https://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: Graph connectivity; Graph orientations; Hypercubes